2002
DOI: 10.1016/s0014-5793(02)03545-7
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a novel proteolysis resistant vascular endothelial growth factor165 variant by a site‐directed mutation at the plasmin sensitive cleavage site

Abstract: Vascular endothelial growth factor (VEGF) is a potent angiogenic mediator in tissue repair. In non-healing human wounds plasmin cleaves and inactivates VEGF 165 . In the present study, we generated recombinant VEGF 165 mutants resistant to plasmin proteolysis. Substitution of Arg110 with Ala110 or Gln110, and Ala111 with Pro111 yielded plasmin-resistant and biologically active VEGF 165 mutants. In addition, substitution of Ala111 with Pro111 resulted in a substantial degree of stabilization when incubated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 29 publications
1
55
0
2
Order By: Relevance
“…12,14,15 Loss of the carboxyl-terminal heparin binding domain through plasmin digestion significantly reduces VEGF165 mitogenic activity on human umbilical vein endothelial cells, supporting the crucial significance of the heparin-binding domains for VEGF-A function. 12,15 So far, little is known about the prevalence and biological significance of proteolytic digestion of VEGF-A in vivo.…”
Section: Inactivation Of the Plasmin Cleavage Sitementioning
confidence: 78%
See 2 more Smart Citations
“…12,14,15 Loss of the carboxyl-terminal heparin binding domain through plasmin digestion significantly reduces VEGF165 mitogenic activity on human umbilical vein endothelial cells, supporting the crucial significance of the heparin-binding domains for VEGF-A function. 12,15 So far, little is known about the prevalence and biological significance of proteolytic digestion of VEGF-A in vivo.…”
Section: Inactivation Of the Plasmin Cleavage Sitementioning
confidence: 78%
“…11,12,14,15 Plasmin digestion of VEGF165 yields two fragments: an amino-terminal homodimer (VEGF1-110) containing the VEGF receptor binding site and a carboxyl-terminal polypeptide comprising the heparinbinding domains (VEGF111-165). 12,14,15 Loss of the carboxyl-terminal heparin binding domain through plasmin digestion significantly reduces VEGF165 mitogenic activity on human umbilical vein endothelial cells, supporting the crucial significance of the heparin-binding domains for VEGF-A function. 12,15 So far, little is known about the prevalence and biological significance of proteolytic digestion of VEGF-A in vivo.…”
Section: Inactivation Of the Plasmin Cleavage Sitementioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing evidence that the persisting infiltration of neutrophils and macrophages plays a major role in the generation of a protease rich and prooxidant hostile microenvironment (21)(22)(23). Recent experimental and several comprehensive clinical studies demonstrated that the proteolytic activity of matrix metalloproteinases and serine proteinases is significantly upregulated in the exudate of chronic wounds (24)(25)(26)(27), thus contributing to the degradation of extracellular matrix molecules (24,25), growth factors and their receptors (28)(29)(30). In addition, proteolytic degradation products generated by high protease activity in the chronic wound environment may exert inhibitory effects on cell function (31).…”
Section: Mechanisms Of Impaired Healingmentioning
confidence: 99%
“…Administration of recombinant TIMP-2, a metalloproteinase inhibitor, promoted tissue repair in a rat model (128). Along these lines, our group generated a novel protease resistant VEGF165 molecule, which is characterized by an increased stability in the protease rich microenvironment of the chronic wound (28,129). This VEGF mutant is expected to exert superior angiogenic properties at the chronic wound site.…”
Section: Candidate Genes For Tissue Repair: a Perspectivementioning
confidence: 99%